2020
DOI: 10.1186/s13018-019-1537-7
|View full text |Cite
|
Sign up to set email alerts
|

Different spinal subtypes with varying characteristics of lumbar disc degeneration at specific level with age: a study based on an asymptomatic population

Abstract: Background: The relationship between spinal sagittal subtypes and lumbar disc degeneration is unclear. Thus, we aimed to investigate the relationship between lumbar intervertebral disc degeneration and age in asymptomatic healthy individuals with different sagittal alignments. Methods: In this cross-sectional observational study, we examined 209 asymptomatic young and middle-aged volunteers (123 women and 86 men) who were divided into the following three groups according to age: groups A (20-30 years), B (31-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
(44 reference statements)
0
2
0
1
Order By: Relevance
“…These findings raise the hypothesis that lower degrees of degeneration in higher lumbar discs produce a more pronounced pain effect and a greater impact on clinical dysfunction and quality of life. A previous study 31 demonstrated that disc degeneration in the upper lumbar spine is more frequent in certain types of spine curvature or certain types of posture, with rectification of the thoracolumbar transition. These situations cause an overload on the disc, and, due to the anatomical configuration of the lumbar spine, there is a smaller dispersion of forces on the disc to the articular facets and other support structures.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These findings raise the hypothesis that lower degrees of degeneration in higher lumbar discs produce a more pronounced pain effect and a greater impact on clinical dysfunction and quality of life. A previous study 31 demonstrated that disc degeneration in the upper lumbar spine is more frequent in certain types of spine curvature or certain types of posture, with rectification of the thoracolumbar transition. These situations cause an overload on the disc, and, due to the anatomical configuration of the lumbar spine, there is a smaller dispersion of forces on the disc to the articular facets and other support structures.…”
Section: Discussionmentioning
confidence: 95%
“…Esses achados levantam a hipótese de que graus menores de degeneração em discos lombares mais altos produzem um efeito álgico mais acentuado e um maior impacto na disfunção clínica e na qualidade de vida. Um estudo anterior 31 demonstrou que a degeneração discal na coluna lombar alta é mais frequente em certos tipos de curvatura da coluna ou certos tipos de postura, com retificação da transição toracolombar. Essas situações propiciam uma sobrecarga no disco, e, devido à configuração anatômica da coluna lombar alta, há uma menor dispersão das forças sobre o disco para as facetas articulares e as demais estruturas de sustentação.…”
Section: Discussionunclassified
“…On average, the incidence of degenerative disc disease is equally common in both men and women of up to 50 years of age. However, the first signs appear earlierat about 25-35 years [2].…”
Section: Introduction/вступmentioning
confidence: 94%
“…Alguns autores já haviam atentado para a ocorrência de maior degeneração do D.I. L1-L2 em determinados padrões de equilíbrio sagital, com retificação da transição toracolombar64 .…”
unclassified